Pelatihan Pemanfaatan Pepaya Grade C sebagai Biostimulan dan Daun Pepaya sebagai Biopestisida di KWT Kenanga Ngestiharjo - Devina Afrilia; Ahmad Rahmadani; Wayan Laudya Cintya Maharani; Yovi Avianto (I-Com: Indonesian Community Journal, 2025)
The Women Farmers Group (KWT) Kenanngga Ngestiharjo faces the problem of low levels namely agricultural productivity due to pest attacks and unutilized agricultural waste. This topic was chosen to explore the use of grade C papaya and rotten papaya as biostimulants, as well as fallen papaya leaves as biopesticides because the use of local materials can increase agricultural yields in a sustainable manner. The methods used include training and assistance in making biostimulants and biopesticides from papaya. The results showed that the use of grade C and rotten papaya was effective in increasing plant growth, while papaya leaves were proven to reduce pest attacks. These findings provide practical solutions for farmers to manage agriculture more environmentally friendly. In conclusion, the use of papaya waste has great potential to increase productivity and reduce dependence on chemical pesticides